Does inclusive leadership affect the organizational socialization of newcomers from diverse backgrounds? The mediating role of psychological capital - Dai, Xinxing; Fang, Yangchun (Frontiers in Psychology, 2023)
Introduction This paper aims to explore the influence of inclusive leadership on the organizational socialization of newcomers from diverse backgrounds, as mediated by psychological capital. Methods Structural equation model was used by Mplus 8.3 to analyze the effect of inclusive leadership and psychological capital on organizational socialization. This study used the 1,000 bootstrap replications method and the mediating path effect test to find out the mediating effect of psychological capital between the relationship of inclusive leadership and organizational socialization. Results The result found that (1) inclusive leadership positively affects newcomers’ organizational culture, interpersonal relationships,socialization into organizational politics and can improve employees’ job competence. (2) Psychological capital plays an intermediary role between inclusive leadership and the organizational culture, interpersonal relationships and socialization into organizational politics and job competence. Inclusive leaders improve newcomers’ psychological capital by encouraging and recognizing their diversity, tolerating their mistakes. It can increase new generation of newcomers’ resilience, self-efficacy and optimism. Individuals with high psychological capital are more likely to integrate into the organizational culture and increase their interaction with colleagues and then are more likely to integrate into the organization. Discussion Organizations should encourage leaders to develop inclusive leadership behaviors to foster newcomer socialization. In an inclusive leadership context, newcomers have high levels of psychological capital that promote their organizational socialization. Inclusive leadership is crucial for helping newcomers from diverse backgrounds to integrate into organizations.